Managing the obligation to stay through employee involvement, recognition and AMO model: a study among millennial employees / Roshidi Hassan, Elaina Rose Johar and Norzanah Mat Nor - Hassan, Roshidi; Johar, Elaina Rose; Mat Nor, Norzanah (Faculty of Accountancy, 2019)
Gaining employee commitment is vital as the knowledge and skills owned by an organisation’s human assets especially the millennial are becoming more pertinent for sustainable competitive advantage. The importance of gaining commitment from these human assets are not just relevant to the large organisation but also to the small as well as growing organisation such as the small and medium enterprises (SMEs). The purpose of this paper is to determine the relationship of human resource (HR) practices (employee involvement, employee recognition) as well as the AMO model towards normative commitment of millennial employees. The study also seeks to provide the theory-based empirical evidence of AMO model as a mediator in achieving the commitment of employees and used Social Exchange Theory (SET) in order to explain the theoretical rationale of the study model. A total of 168 employees participated in this study, which was selected using systematic random sampling to represent SMEs service sectors in Selangor. The PLS-SEM was utilised in order to explain the relationship among HR practices towards normative commitment as well as AMO model as a mediator. A key finding that emerged from the analysis showed that both employee involvement and employee recognition have direct relationship towards the normative commitment and AMO model does not play an important role in gaining normative commitment as it does not mediates any of the relationship. The research study undoubtedly offered profound understanding to organisation that employees feel an obligation to stay in the organisation only by involving and recognising them well.